The analysis of strategic planning in transport - Išoraite, Margarita (Transport, 2006)
Strategic planning is a process whish brings to life the mission and vision of an enterprise. The article analyses the following issues: 1. Concepts of strategy. 2. Components of strategic planning. 3. The basis of strategic planning. 4. Formal strategic planning. 5. Tools used in strategy development. 6. Problems of strategic planning.First Published Online: 27 Oct 2010